POLD2 is activated by E2F1 to promote triple-negative breast cancer proliferation - Zhang, Zhen (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) is a highly malignant breast cancer subtype with a poor prognosis. Improved insight into the molecular biology basis of TNBC progression is urgently needed. Herein, we reported that POLD2 was highly expressed in TNBC and patients with high POLD2 expression in their tumors had poor clinical outcomes. In functional studies, knockdown of POLD2 inhibited the proliferation of TNBC. Mechanistically, we revealed that transcription factor E2F1 directly bound to the promoter of POLD2 and regulated its expression in TNBC cells, which in turn contributed to the proliferation of TNBC. Additionally, rescue experiments validated that E2F1-mediated cell proliferation in TNBC was dependent on POLD2. Taken together, our results elucidated a novel mechanism of the E2F1-POLD2 axis in TNBC proliferation, and POLD2 may be a potential therapeutic target for TNBC treatment.